The Effect of Head Rotation on Intraocular Pressure in Prone Position: a Randomized Trial - M. Nuri Deniz; Arzum Erakgün; Nezih Sertöz; Suzan Güven Yılmaz; Halil Ateş; Elvan Erhan (Brazilian Journal of Anesthesiology, 2013)
Background and objectives: The increased intraocular pressure (IOP) - which decreases perfusion pressure on the optic nerve - increases by prone positioning (1). The aim of our study was to compare the effect of head rotation 45° laterally in prone position on the increase in IOP of upper placed and lower placed eyes in patients undergoing percutaneous nephrolithotomy (PCNL). Methods: Forty-ﬁve patients were randomly divided into 2 Groups. IOP of the patients were recorded bilaterally in supine position before the operation had started. Patients were turned to prone position. The head was placed on a prone headrest without external direct compression to both eyes. Patients in Group I were kept in strictly neutral prone position where as patients in Group II were placed prone with their heads rotated 45° laterally to the right side. At the end of the operation, patients were turned to supine position and their IOP was measured immediately. Results: There was no difference related to demographics, duration of surgery, blood loss and ﬂuid input data. IOP values after surgery in prone position increased signiﬁcantly compared to preoperative values in both groups (p < 0.05). After surgery in prone position IOP values of the upper positioned eyes in Group II were signiﬁcantly lower than Group I and lower positioned eyes in Group II (p < 0.05). Conclusion: prone positioning increases IOP. In patients with prone position with a head rotation of 45o laterally, IOP in the upper positioned eye was signiﬁcantly lower. Keywords: Intraocular Pressure, Head Movements, Rotation, Prone position